DNA isolation and amplification of raru leaf (Cotylelobium melanoxylon Pierre and Cotylelobium lanceolatum Craib). Issue 1 (March 2021) - Susilowati, A; Rachmat, H H; Elfiati, D; Rangkuti, A B; Yulita, K S; Dwiyanti, F G; Fambayun, R A; Gea, P; Ginting, I M
Abstract: Cotylelobium lanceolatum Craib and Cotylelobium melanoxylon Pierre or locally known as raru are trees used as ingredients for traditional Batak drinks called "tuak". Destructive and uncontrolled harvesting of raru leads to a decline in its population and genetic diversity. Morphological distinctions for C. melanoxylo n and C. lanceolatum have been conducted even though there are some weaknesses of this identification, thus molecular based marker are tools which is preferred for solved the problem. However, an appropriate DNA isolation method is basic and important step for molecular studies to obtain high-quality genomic DNA so that further analysis can proceed. Therefore, our study focused to obtain the successful DNA isolation method using the modified CTAB ( Cetyl Trimethyl Ammonium Bromide ) method and its amplification on three candidate of DNA barcodes i.e. trn L- trn F, trn H- psb A, ITS1-ITS4. In total six genomic DNA were isolated from the silica-gel dried leaf of the two raru species and amplified with trn L- trn F, trn H- psb A, and ITS1-ITS4 primer-pairs. The results showed that the modified CTAB method proved to be successful and applicable for the extraction of DNA of C. melanoxylon Pierre and C. lanceolatum Craib. Furthermore, the trn L- trn F primer-pair was successfully amplified compared with trn H- psb A and ITS 1- ITS 4 indicating that the primer-pair can be used as a DNA barcode candidate for further DNA sequencing and analysis.